1981
DOI: 10.1177/00220345810600100801
|View full text |Cite
|
Sign up to set email alerts
|

TEM Study of the Central Dark Line in Enamel Crystallites

Abstract: The dark line which is observed in enamel crystallites represents a planar defect involving a single 100 plane of the hydroxyapatite structure. It may occur in the majority of crystals throughout the enamel, although it is only observed in specific diffraction conditions. Its presence may be related both to the formation and growth of crystallites in the developing tooth and to the manner in which the crystallites dissolve during caries. TEM studies show clearly that the central defect is not a dislocation, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 13 publications
5
32
0
Order By: Relevance
“…It is, however, still not clear if this phase transformation takes place through an internal structural rearrangement of the metastable phase or by dissolution/ reprecipitation. Ever since the dark line observed in the center of enamel crystals 198 was shown to be OCP phase, it has been speculated that it should be a remnant of the OCP phase composition of either the initially precipitated or the most dominant transitory phase. 199,200 Claims that the precipitated apatite is normally a solid solution rather than a double salt of OCP and HAP may speak in favor of partial or complete transition between these CAP phases in the solid state.…”
Section: Mechanism Of Formation Of Hap By Precipitationmentioning
confidence: 99%
“…It is, however, still not clear if this phase transformation takes place through an internal structural rearrangement of the metastable phase or by dissolution/ reprecipitation. Ever since the dark line observed in the center of enamel crystals 198 was shown to be OCP phase, it has been speculated that it should be a remnant of the OCP phase composition of either the initially precipitated or the most dominant transitory phase. 199,200 Claims that the precipitated apatite is normally a solid solution rather than a double salt of OCP and HAP may speak in favor of partial or complete transition between these CAP phases in the solid state.…”
Section: Mechanism Of Formation Of Hap By Precipitationmentioning
confidence: 99%
“…Figure 4(a) shows a typical HRTEM image of mineral needles extracted from human cortical bone. The FFT analysis revealed the lattice fringes of the needles as HA with the [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] zone axis and suggested that the needle direction was parallel to the (1-100) plane of HA [ Fig. 4(b)].…”
Section: (A)]mentioning
confidence: 99%
“…Generally, hard tissue-forming cells-such as ameloblasts, odontoblasts and osteoblasts-are responsible for the development of various sized apatite crystals suited to different hard tissues (e.g., large crystals in enamel and small crystals in dentin and bone). In addition, the process of crystal formation under normal conditions is strictly regulated by cellular activities that either produce crystals with CDLs in various hard tissues [23][24][25][26][27][28] or without CDLs in the tooth enamel of fish and tooth apparatus of conodonts 29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…According to our recent findings, apatite crystals can be crystallographically divided into 2 types: (1) crystals with central dark lines (CDLs), formed in normal calcified hard tissues of vertebrates [23][24][25][26][27][28] , and (2) crystals without CDLs, formed, for example, in the tooth enamel of fish and tooth apparatus of conodonts 29,30) . Hard tissue-forming cells thus either produce crystals with CDLs or without CDLs.…”
Section: Introductionmentioning
confidence: 99%